Cuba in the Western Hemisphere: What Has Changed?. (1st December 2015) - Carlos Oliva Campos; Gary Prevost
Abstract : On 17 December 2014, the presidents of Cuba and the US, Raúl Castro and Barack Obama, announced simultaneously to the world the decision of an exchange of prisoners releasing the three Cuban intelligence operatives still in jail in American prisons – Gerardo Hernández, Ramón Labañino and Antonio Guerrero – and the subcontractor Alan Gross, imprisoned in the island. Together with Gross, a CIA agent of Cuban origin was also released, and an agreement was reached to set free certain opponents of the Cuban government. The unexpected news was the decision to re-establish the bilateral diplomatic relations broken for more than 50 years. This article places the re-establishment of full diplomatic relations between Cuba and the US in the context of changing political relations in the Western Hemisphere culminating in Cuba's historic participation in the seventh Summit of the Americas in Panama in April 2015. The authors argue that growing independent-minded thinking of key Latin American countries and their progressive leaders was a key factor in explaining Obama's overture to Cuba in the absence of any fundamental concessions from the Cuban side.